Promotion of technologies for the integrated management of plantain to improve farm productivity: final report submitted by the International Institute of Tropical Agriculture covering the period 14 March 2012 to 30 April 2014 - Fotso Kuate, A.; Ngatat, S.E.; Lienou, J.; Membang, G.; Assiedu, E.; Hanna, R. (2014)
The International Institute of Tropical Agriculture (IITA) and the African Center for Research on Banana and Plantain (CARBAP) signed an agreement on 14 March 2012 within the framework of the CORAF/WECARD project entitled "Promotion of integrated crop management technologies to improve plantain productivity of smallholder farmers." This report summarizes activities undertaken, covering the field survey, the creation of innovation platform, the establishment of field trials, training and capacity building in IPM and ISFM and the continued monitoring of the trials with the participation of members of the platforms. The socioeconomic surveys and accompanying visits for the two target regions –South and Center - was completed. A total of 125 questionnaires were administered and 84 fields were visited in a total of 31 villages in the two regions covered by the surveys. Data are being used by research to develop sustainable control measures to tackle identified constraints. Tissue culture plants of six varieties were received from CARBAP in May 2012. Losses during acclimatization were considerably high which allowed the establishment of one EVP and one EVM trials in September 2012. Farmers are now interested in getting new varieties following first cycle evaluation. The soil fertility experiments initiated in April and May 2012 and in each zone of the project was monitored on a monthly basis. Organic fertilizer in the form of poultry manure resulted in the greatest first cycle plantain bunch weight compared with mulching with Tithonia and synthetic fertilizer. This has been adopted by farmers in establishing their new fields. Training sessions on the PIF propagation technique, plantain cultivation practices, IPM and ISFM was organized for the platform members in Ambam and Ntui and we monitored the training of producers by trainers. Plants produced are being used to establish new fields and the selling of produced plant is also generating revenues for families. Production of PIF from local and improved varieties is ongoing and the innovation platforms are being animated by IITA. Distribution of planting materials and training on IPM and ISFM were done during the first quarter of 2013. We established 1ha plantain multiplication fields in Ambam and Ntui with both Hybrid and local plantain. These fields are being used by platform members as traceable source of sucker for macropropagation. Individual propagators are being replicated the then intervention area and new fields with clean plant are being established. Evaluation of varieties in the EVM was done with the participation of farmers from the two platforms. They evaluated the plantain characteristics on the farm and tasted the different preparation made out of the 8 varieties. Monitoring of the trainers will be intensified in 2014 by offering trainers a training kit so that they can continue to train producers on macropropagation, IPM and ISFM. Evaluation of the variety participatory trials by the farmers is also planned, as well the second cycle evaluation of the fertility trial. Macropropagation of the improved varieties selected by farmers from the variety trials will be initiated and plants will be distributed to farmers.